Service Oriented and Cloud Computing : 4th European Conference, ESOCC 2015, Taormina, Italy, September 15-17, 2015, Proceedings - Dustdar, Schahram; Leymann, Frank; Villari, Massimo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Infotext: This book constitutes the refereed proceedings of the 4th European Conference on Service-Oriented and Cloud computing, ESOCC 2015, held in Taormina, Sicily, Italy, in September 2015. The 13 research papers, three industry papers, and two work-in-progress papers presented were carefully reviewed and selected from 48 submissions. The papers are organized in topical sections on cloud technology, service composition, software development and cloud technology, cloud computing, and industry track.
Keywords: Software engineering; Information storage and retrieva; Computer security; Information Systems; Database management; Information technology; Software Engineering; Information Storage and Retrieval; Systems and Data Security; Management of Computing and Information Systems; Database Management; IT in Business